2018
DOI: 10.3389/fcell.2018.00058
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional Modulation of Sphingosine-1-Phosphate Receptor 1 by miR-19a Affects Cardiovascular Development in Zebrafish

Abstract: Sphingosine-1-phosphate is a bioactive lipid and a signaling molecule integrated into many physiological systems such as differentiation, proliferation and migration. In mammals S1P acts through binding to a family of five trans-membrane, G-protein coupled receptors (S1PRs) whose complex role has not been completely elucidated. In this study we use zebrafish, in which seven s1prs have been identified, to investigate the role of s1pr1. In mammals S1PR1 is the most highly expressed S1P receptor in the developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In Zebrafish, mutations in s1pr2, but not any of the other S1P receptors, led to cardia bifida or formation of two laterally positioned hearts (22) (Summarized in Figure 1). This phenotype was also observed in multiple studies with a spns2 mutant or overexpression of s1pr1 (22)(23)(24)(25)(26)(27)(28)(29). In mice, conditional knockout (KO) of S1PR1 caused embryonic lethality due to ventricular non-compaction, ventricular septal defects, absence of normal increase in the number of cardiomyocytes and decreased myofibril organization (28).…”
Section: Sphingolipids In Heart Development and The Cardiac Conductiomentioning
confidence: 81%
See 2 more Smart Citations
“…In Zebrafish, mutations in s1pr2, but not any of the other S1P receptors, led to cardia bifida or formation of two laterally positioned hearts (22) (Summarized in Figure 1). This phenotype was also observed in multiple studies with a spns2 mutant or overexpression of s1pr1 (22)(23)(24)(25)(26)(27)(28)(29). In mice, conditional knockout (KO) of S1PR1 caused embryonic lethality due to ventricular non-compaction, ventricular septal defects, absence of normal increase in the number of cardiomyocytes and decreased myofibril organization (28).…”
Section: Sphingolipids In Heart Development and The Cardiac Conductiomentioning
confidence: 81%
“…At later developmental stages, knockdown of the zebrafish gene homolog to s1pr1 caused an improperly looped heart (30,31). Another study showed that an s1pr1 morpholino in zebrafish affected heart valve orientation, an indicator of incorrect looping (28). During the looping process, precursors of cardiac valves-endocardial cushioning (EC) and atrioventricular canal (AV)-are also formed.…”
Section: Sphingolipids In Heart Development and The Cardiac Conductiomentioning
confidence: 99%
See 1 more Smart Citation
“…s1pr1 levels are normally suppressed by microRNA (miR)-19a, and when levels of this microRNA are decreased, higher s1pr1 expression causes impaired cardiac looping, abnormal chamber shapes, and downregulation of cardiac precursor genes. s1pr1 upregulation appears to mediate the detrimental effects on cardiac and fin development normally caused by T-box transcription factor 5 ((Tbx5) and subsequent miR-19a) depletion [ 249 ]. In mice, the situation appears to be much simpler, as shown by a recent report that utilized Cre-mediated conditional knockout of the S1P receptor 1 in developing embryos.…”
Section: Recent Advances In Bioactive Lipids In Cardiac Developmenmentioning
confidence: 99%
“…In zebrafish, cardiac defects generated by Tbx5 depletion can be partially reverted by modulation of miR-19a, a member of this cluster, in line with a role of this miRNA as Tbx5 functional effector. Furthermore, miR-19a is able to affect heart rate control in Holt-Oram syndrome [HOS] fish by targeting the Sphingosine-1-Phosphate Receptor 1 which is highly expressed in mammalian cardiomyocytes and implicated in numerous cardiovascular processes [32]. Moreover miR-17-92 cluster has been also shown to directly repress genes, such as SHOX2 and TBX3, that are required for sinoatrial node development while miR-1 also targets the zinc finger homeobox 3 gene (ZFHX3) which is another important AF susceptibility-conferring gene [33][34][35].…”
Section: The Interplay Between Mirnas and Transcription Factorsmentioning
confidence: 99%